The Rainfall Intensity Analysis in the Mount Merak Imogiri Area, as a Data-Based Recommendation for Disaster Mitigation and Drainage Managementof Cultural Heritage Sites - Muchamad Arif Budiyanto; Muhamad Arifin; Afnan Juli Arochma (Universitas Negeri Semarang, 2026)
Mount Merak area in Imogiri Bantul Regency, Yogyakarta Special Region, is a highly important historical and cultural site. Its existence is located on a hillside with a terraced topography, making it vulnerable to the impact of hydrometeorological events (such as extreme rain). The aim of this research is to measure and analyze the intensity of rain in the Mount Merak Imogiri area. Provide data-based recommendations for hydrometeorologicaldisaster mitigation strategies, especially related to drainage management and erosion prevention. The methodology used involves frequency analysis of maximum daily rainfall data for 20 years (2004–2023) from the Siluk Rain Post which was processed using MS Excel software. The selection of the best distribution model was based on the Chi-Square and Smirnov- Kolmogorov goodness-of-fit tests, which determined the Log-Normal distribution as the most suitable method. Results of calculating rain intensity using the Mononobe method taking into account the concentration time (Tc) of 4.91 minutes. The analysis results show that the rainfall intensity value for return periods 2, 5, 10, 20, 50 and 100 years respectively is 15.71; 19.40; 21.66; 23.73; 24.37; and 26.29 mm/hour. These findings indicate a high risk of surface runoff in a short duration, so it is necessary to design optimal drainage systems and strengthen slopes to maintain the stability of cultural heritage building structures from the threat of local erosion and flooding.